Synchronicity: Pushing the envelope of fine-grained localization with distributed MIMO - XIONG, Jie (Institutional Knowledge at Singapore Management University, 2014)
Indoor localization of mobile devices and tags has received much attention recently, with encouraging fine-grained localization results available with enough line-of-sight coverage and enough hardware infrastructure. Synchronicity is a location system that aims to push the envelope of highly-accurate localization systems further in both dimensions, requiring less line-of-sight and less infrastructure. With Distributed MIMO network of wireless LAN access points (APs) as a starting point, we leverage the time synchronization that such a network affords to localize with time-difference-of-arrival information at the APs. We contribute novel super-resolution signal processing algorithms and reflection path elimination schemes, yielding superior results even in non-line-of-sight scenarios (with one to two walls separating client and APs). We implement and briefly evaluate Synchronicity on the WARP hardware radio platform using standard 20~MHz wireless LAN channels.